ASPEK NEUROANATOMI DAN IMPLIKASI KLINIS SINDROM BALINT - Restu Susanti,* Yuliarni Syafrita* (Neurona Majalah Kedokteran Neuro Sains, 2016)
SYNDROME IS A NEUROPSYCHOLOGICAL DISORDER CAUSE BY BILATERAL POSTERIOR PARIETAL LOBE DAMAGE THIS DISORDER CAN BE CAUSED BY INFARCTION OF THE WATERSHED AREA CAUSED BY STROKE HEAD TRAUMA HYPOXIA ENCEPHALOPATHY ALZHEIMERS OR OTHER CEREBRAL LESIONS THE CLINICAL FEATURES OF THIS SYNDROME CONSISTS OF SIMULTANAGNOSIA OPTIC ATAXIA AND APRAXIA OCULI IT CAN ALSO BE ACCOMPANIED WITH INFERIOR VISUAL FIELD DISTURBANCES AND BILATERAL HEMINEGLECT